PENGARUH MOTIVASI KERJA GURU DAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU SMP NEGERI DI KECAMATAN COMAL KABUPATEN PEMALANG - Rumaeni Rumaeni; Soegito Soegito; Nurkolis Nurkolis (Jurnal Manajemen Pendidikan (JMP), 2016)
Problems in this study were: (1) is there any influence between work motivation on work discipline junior high school teachers throughout the District Comal State, (2) to analyze the influence of managerial competence principals to teachers working discipline Junior High School Comal District of Pemalang, (3) analyze the influence between work motivation of teachers and school heads managerial competencies simultaneously to work discipline Junior High School teacher throughout the District Pemalang. Results showed the: (1) correlation of variables X1 to Y by 0,266 is very low, with a value of R2 is 0,071 means that the effect of variable X1 on Y is equal to 7,1%. (2) correlation X2 on Y of 0,407 is middle, with a value of R2 is 0,166 means that the effect influence of X2 on Y is equal to 16,6%. (3) the results of multiple regression analysis obtained by the amount of the value of R2 is 0,175 means that the effect influence of the variables X1 and X2 into Y is 17,5%, while the other variables that influence amounted to 28.4%, with the regression equation Y = 2,805 + 0,097 X1 + 0,268 X2.